2018
DOI: 10.1080/17435390.2018.1451568
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dissolved and nanoparticulate Ag effects on the life cycle of an estuarine meiobenthic copepod, Amphiascus tenuiremis

Abstract: Many nanotoxicological studies have assessed the acute toxicity of nanoparticles (NPs) at high exposure concentrations. There is a gap in understanding NP chronic environmental effects at lower exposure concentrations. This study reports life-cycle chronic toxicity of sublethal exposures of polyvinylpyrrolidone-coated silver nanoparticles (PVP-AgNPs) relative to dissolved silver nitrate (AgNO) for the estuarine meiobenthic copepod, Amphiascus tenuiremis, over a range of environmentally relevant concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…A developmental rate of 0.28 d –1 was determined in both natural seawater and SWW (10% SWW in natural seawater) controls, and this value was set to represent 100%. An increased toxicity was observed upon exposure to the positive AgNO 3 control, resulting in an EC 50 of 9.86 μg/L (Figure S2), which is in the same range as in previous studies with the copepod Amphiascus tenuiremis and confirms the increased sensitivity of the naupliar developmental stage. Exposure to increasing concentrations of Ag NPs led to delayed development at concentrations above 500 μg/L with a complete cessation of molting and increased mortality (Figure A).…”
Section: Results and Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A developmental rate of 0.28 d –1 was determined in both natural seawater and SWW (10% SWW in natural seawater) controls, and this value was set to represent 100%. An increased toxicity was observed upon exposure to the positive AgNO 3 control, resulting in an EC 50 of 9.86 μg/L (Figure S2), which is in the same range as in previous studies with the copepod Amphiascus tenuiremis and confirms the increased sensitivity of the naupliar developmental stage. Exposure to increasing concentrations of Ag NPs led to delayed development at concentrations above 500 μg/L with a complete cessation of molting and increased mortality (Figure A).…”
Section: Results and Discussionsupporting
confidence: 86%
“…Increased Ag toxicity to Daphnia magna has also been previously observed in the presence of TiO 2 with higher Ag body burdens that were explained by ingestion of Ag-sorbed TiO 2 NPs 40 . In the current study, the observed differences in toxicity are suggested to be due to the dynamic nature of the exposures, where organisms are being exposed to (i) a mixture of both particles and dissolved species released over time and (ii) different particulate complexes formed over time, which is in agreement with previous studies 39 . It should be noted that the NP behavior and subsequent exposure to T. battagliai may be altered by the presence of the algae.…”
Section: Effects Of Particles On T Battagliai Naupliar Developmentsupporting
confidence: 91%
See 2 more Smart Citations
“…Benthic copepods are used in a range of studies, to evaluate how exposure to chemical stressors can be associated to effects on reproductive success, fecundity, and development of different species, such as the genus Nitocra spp. (Izar et al, 2019;Cariello, 2018;Perina, 2018), Tisbe biminiensis (Araújo-Castro, et al, 2009;Maciel, 2015;Régis, 2018), and Amphiascus tenuiremis (Sikder, 2018; Organisation for Economic Cooperation and Development, 2007). These detritivore filter feeding organisms constitute an important component of the marine trophic chain, linking the energy and biomass flow from the primary producers to the consumers, since they represent relevant dietary items for diverse marine organisms, such as fish (special fingerlings and post larvae) and other crustaceans (Ruppert et al, 1996).…”
Section: Introductionmentioning
confidence: 99%